Influence of quality and physiological coloration of guandu bean seeds (Research, Society and Development, 2020)
The objective of this study was to study the physiological quality of guandu bean seeds submitted to different drying temperatures (40, 50, 60, 70 °C), besides the coloration of the seeds in different moisture contents during the drying process. The experiment was carried out at the Phytotechnic Laboratory, Seed Laboratory and the Post Harvest Laboratory of IFGoiano - Campi Iporá and Rio Verde, respectively. To evaluate the physiological quality, the germination test, germination speed index and electrical conductivity were performed. To analyze the color of the seeds, they were submitted to drying until reaching the water content of 12% wet basis (wb). Guandu bean seed color was evaluated by direct reflectance reading of the “L”, “a” and “b” coordinates, using the ColorFlex EZ colorimeter. Concluding that high temperatures reduce the drying time, however the best indicated temperature for drying guandu bean seeds without affecting the physiological quality is between 40 and 50 °C, and high temperatures cause greater damage to the seed, consequently reducing its quality. The reduction in water content provided a variation in the “L”, “a” and “b” coordinates of the pea bean seeds.